Let a thousand flowers bloom: A short note on the multidimensional benefits of Chinese immigrants to Canada - Don J. DeVoretz (Institute of Labor Economics (IZA), 2020)
A rise in Chinese immigrant arrivals would have respectively decisive and unambiguous positive socio-economic effects on Canadians. The multidimensional positive impacts accruing to Canada from the increased arrival of Hong-Kong, Taiwanese and PRC immigrants would be manifested in terms of the long term presence of highly educated immigrants increasing Canada's productivity which will in turn diversify Canada's trade patterns beyond Canada's current NAFTA/USMCA boundaries. Cultural enrichment in terms of increased financial and artistic support for Canada's fine arts and musical world would also be encouraged by an increased presence of Chinese immigrants in Canada's cultural milieu.
Keywords: J60; J61; J68; 330; immigration policy; Canada; cultural enrichment